Correlation between Levels of Remnant Cholesterol versus LDL, A Cross-Sectional study (International Journal of Scientific Research and Management (IJSRM), 2022)
Background: High levels of LDL cholesterol were directly related to the risk of atherosclerosis, metabolic diseases, and cardiovascular complications. However, in some groups of patients with low levels, they were also found. Lead to the risk of other lipid components, including Remnant cholesterol. A recent study found related to cardiovascular risk as well. Currently, no direct comparison between Remnant cholesterol and LDL cholesterol level. Objective: To study the correlation between Remnant cholesterol and LDL levels both in fasting and non-fasting states with the medical conditions that increase the risk of cardiovascular disease. Materials and methods: To determine the association between remnant cholesterol and LDL. 200 cases of Thai begins at the age of 18 years old were tested for total cholesterol, LDL, HDL, and TG level both in the fasting and non-fasting states. The obtained values were calculated for Remnant cholesterol levels and analysed for a direct correlation between the two levels, which also includes a comparative analysis. The AUC was used to assess the prognostic accuracy of lipid levels to diagnose the condition that poses cardiovascular risks. Results: In the sample of 200 patients tested for lipid. At a mean age of 64.5 years, 42 percent were female and 76.5 percent received statins. We found that remnant cholesterol had a poor correlation with LDL levels when compared among the fasting conditions (r=0.164, 0.119), as well as among the statin used or not (r=0.118, 0.293). The analysis found that remnant cholesterol does well correlate with TG levels (r=0.770). Also, the predictive value of Remnant cholesterol over LDL levels for detect diabetes mellitus, coronary artery disease, and overweight (AUC=0.610, 0.588, 0.593). Conclusion: In this study. We found that remnant cholesterol does correlate poorly with LDL in any fasting state. Prediction of the incidence of diabetes mellitus, coronary heart disease, and overweight has seemed better with remnant cholesterol. More studies may need for decreasing the knowledge gap and provide a better guide for disease prevention.